High-efficiency immunoassay platforms with controllable surface roughness and oriented antibody immobilization1. Issue 38 (14th October 2015) - Song, Lingjie; Zhao, Jie; Luan, Shifang; Ma, Jiao; Ming, Weihua; Yin, Jinghua
<x xml:space="preserve">Abstract</x> High-efficiency immunoassay platforms were facilely prepared by combining a layer-by-layer particle deposition with site-specific antibody immobilization through boronic acid moieties.